Religious Harmony in India: Exploring the Enlightened Approaches of Sir Syed Ahmad Khan and Wahiduddin Khan - Shakeel Ahmad Lone; Mushtaq Ahmad Nadaf (Penerbit Hellow Pustaka, 2023)
Throughout multi-religious societies, living peacefully and maintaining harmony and integrity are key requirements. Peace is not merely the absence of war; it has much more socio-psychic connotations that involve all aspects of holistic existence. Religious harmony simply means the peaceful coexistence of different religions and their followers. Peace and religious harmony in India have been topics of great significance due to the country's diverse religious landscape. The nation's history has had some occasions for racial struggle and religious conflict. But there have also been people from multiple religions throughout history who have worked continuously to promote peace and harmony by encouraging acceptance and understanding of those of various faiths. Foremost among these stalwart figures are Sir Syed Ahmad Khan and Maulana Wahiduddin Khan, whose progressive outlooks had a profound effect on India's religious structure. Sir Syed's efforts were rooted in modern education, so he advocated that